Location-specific labour control strategies in online retail - Martina Fuchs; Peter Dannenberg; Tatiana López Ayala; Cathrin Wiedemann; Tim Riedler (ZFW - Advances in Economic Geography, 2023)
Online retail is currently profoundly restructuring the working conditions in the retail sector. Existing studies generally describe the working conditions in the large warehouses of online retail as 'digital Taylorism'. This article broadens this perspective and draws on the theoretical concept of the local labour control regime. It explores how managements' technological and social labour control strategies vary spatially between online retail warehouses located in inner and outer metropolitan areas of the four largest German cities. The study uses qualitative methods and is mainly based on expert interviews with executives, representatives of trade unions and works councils, representatives of associations, and further experts. This study gains insights on the spatial variety of labour control and thus is relevant for international research on labour control and for practitioners' ability to create decent and humane work.
Keywords: 330; e-commerce; economic geography; labour geography; labour union; metropolitan area; Online retail